Rust Resistance In Soybean Linked To Higher Leaf Manganese Content (Journal of Plant Disease Sciences, 2018)
The Asian soybean rust caused by Phakopsora pachyrhizi has attained the status of important biotic factor causing significant loss in seed yield. Systematic study of the various physiological and biochemical factors, contribute to the resistance of the soybean rust is required to be studied. Hence, an attempt has been made to invade into the mechanisms in the background of foliar application of manganese sulphate (MnSO4) and potassium silicate (K2SiO3) which play a great role in disease resistance. The resistant genotypes recorded higher chlorophyll content. Biochemical studies revealed that resistant genotypes with Mn the treatment manganese sulphate accumulated more total phenols, showed higher antioxidative enzyme activity (polyphenol oxidase and peroxidase). Host plant chitinase activity as such increased in inoculated plants and increased more in manganese treatment. Resistance genotypes inherently contained higher manganese content with higher total phenols, Polyphenol oxidase enzyme , perooxidase and chitinase activity. Mn plays a key role in phenylpropanoid metabolism and could perform defense-related functions. So, it can be concluded that manganese can be used as a nutritive agent to increase resistance in plants against fungal diseases.Resistant genotypes with higher Mn content also gave significantly higher seed yield, higher number of pods, seed weight per plant.
Keywords: Soybean; Peroxidase; Potassium silicate; Rust; Phakopsora pachyrhizi